2020
DOI: 10.21203/rs.2.20890/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phase I study of a dual PI3-Kinase/mTOR inhibitor BEZ235 in adult patients with relapsed or refractory acute leukemia

Abstract: Background Combined inhibition of phosphatidylinositol 3-kinase (PI3K) and the mammalian target of rapamycin (mTOR) complexes may be an efficient treatment for acute leukemia. The primary objective of this phase I single center open label study was to determine the maximum tolerated dose (MTD) and recommended phase II dose (RP2D) of the dual pan-class I PI3K and mTOR inhibitor BEZ235 in patients with advanced leukemia. Methods Herein patients > 18 years of age who had relapsed or showed refractory leukemia … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…With several PI3K/AKT pathway inhibitors in development, [37][38][39][40][41] these data could find clinical applications for high risk T-ALL patients with PI3K/AKT pathway activation in whom stardard treatment does not lead to MRD negativity. Dactolisib (BEZ235) is a dual pan-PI3K and mTOR inhibitor for which a phase I study in acute leukemia showed positive effect in a subset of ALL patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With several PI3K/AKT pathway inhibitors in development, [37][38][39][40][41] these data could find clinical applications for high risk T-ALL patients with PI3K/AKT pathway activation in whom stardard treatment does not lead to MRD negativity. Dactolisib (BEZ235) is a dual pan-PI3K and mTOR inhibitor for which a phase I study in acute leukemia showed positive effect in a subset of ALL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic inhibition of PI3K-AKT signaling showed pronounced anti-proliferative effects and induced apoptosis in preclinical models using leukemia cell lines or primary leukemia samples. [37][38][39][40][41] Given the negative effect of TAL1 on cell growth and the key role of PI3K signaling in TAL1 positive T-ALL, we examined the effect of PI3K-AKT inhibitors in our different models. In agreement with the negative effect of TAL1 on cell growth, we show that inactivation of PI3K/AKT pathway has a stronger effect on viability in TAL1+AKT E17K cells compared to AKT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several compounds targeting this pathway are in clinical trials combined with targeted therapy, endocrine therapy, or cytotoxic agents. 8,9 Silibinin, the main component of silymarin, the natural substance from milk thistle seeds, influences oestrogen receptors and blocks PI3K/Akt/mTOR and Ras/ERK signalling. 10 The anticancer activity of cruciferous vegetables is mainly due to the presence of the phytochemical indole 3 carbinol (I3C).…”
Section: Introductionmentioning
confidence: 99%
“…PI3K/Akt/mTOR signalling pathway is a major focus of interest in breast cancer and is identified as a novel target for drug discovery. Several compounds targeting this pathway are in clinical trials combined with targeted therapy, endocrine therapy, or cytotoxic agents 8,9 . Silibinin, the main component of silymarin, the natural substance from milk thistle seeds, influences oestrogen receptors and blocks PI3K/Akt/mTOR and Ras/ERK signalling 10 …”
Section: Introductionmentioning
confidence: 99%